Penerapan Konsep Shaping Neighborhoods pada Perancangan Distrik Ngupasan dan Ngampilan di Kota Yogyakarta - Hardi, Resty Aprila; Miarsono, Harry (Universitas Pelita Bangsa, 2024)
Yogyakarta, as one of the main tourist destinations in Indonesia, has very strategic and historically rich areas, one of which is the Malioboro Street area which is known as the center of trade and culture. Surrounding this area are two important districts, Ngupasan and Ngampilan, which have strong historical-trade characteristics but are also facing pressure from rapid tourism development. Rapid changes in the social and economic structure of these two districts pose challenges in space management, the quality of life of local communities, and the preservation of cultural identity. This research aims to analyze the application of the shaping neighborhoods concept in the design of Ngupasan and Ngampilan areas in Yogyakarta City. The concept of shaping neighborhoods is expected to provide solutions in creating sustainable areas, integrating various spatial functions, such as residential, public spaces, and commercial areas, as well as promoting social diversity and local community involvement. With this approach, this research also explores how a design based on the principle of shaping neighborhoods can create a balance between the needs of tourism and the sustainability of local communities. The method used in this research is qualitative analysis through literature studies, field observations, and interviews with stakeholders, including city governments, urban planners, as well as local communities and tourism sector actors. The results show that the application of the concept of shaping neighborhoods in these two districts can optimize the function of space, increase social interaction, and strengthen the integration between the social life of local communities with growing tourism activities. This research is expected to provide recommendations for urban planning that is more inclusive, sustainable, and responsive to the dynamics of change in the historical-trade area.